Effect of dilute doping and non-equilibrium synthesis on the structural, luminescent and magnetic properties of nanocrystalline Zn1-xNixO (x = 0.0025 – 0.03). (July 2019) - Mihalache, V.; Negrila, C.; Bercu, V.; Secu, M.; Vasile, E.; Stan, G.E.
Graphical abstract: Highlights: ZnO properties were influenced by both Ni doping and (non-equilibrium) processing conditions. Ni reduces cell volume, Vc, green PL and EPR signal; enhances RTFM, blue PL and FWHM of O1 s. Ni influences the morphology and thermodynamics of ZnO growth. Oxide deficiency and high ZnO formation rate favored VO and Zni formation. Change of concentration of native defects in their charge state influences both Vc and RTFM. Abstract: We report on the influence of dilute doping combined with the processing conditions on the morphological, structural, chemical states, photoluminescence and magnetic properties of Zn1-x Nix O nanopowders. Ni doping changes the ZnO powder morphology from randomly-aggregated nanocrystals to densely-packed nanocrystals arranged in columnar particles, modifies the high-energy-component of O1 s spectrum and increases the modified Auger parameter in XPS, enhances the blue photoluminescence (PL) emission, suppresses the green PL emission and the intensity of the g  = 1.997 EPR signal. Ni-ZnO nanostructures show room-temperature ferromagnetism (implying they can serve as dilute magnetic semiconductors). The saturation magnetization, crystallite size and microstrain increase with the doping level; the c -axis constant and unit cell volume decrease, however, being unexpectedly higher with respect to a (reference) ZnO powder with a relaxed lattice. We demonstrate that the investigated properties were controlled by both (dilute) doping level and donor native defects produced by non-equilibrium (oxygen-deficiency and high rate of) ZnO formation.